Case studies in anatomy: upper limb - Tun, Ye; Myint, Yi Yi (IIUM Press, 2012)
Anatomy, as a part of the medical school curriculum, has always been recognized as an essential foundation for the clinical sciences. It forms a basis for the study of the normal structure for the subsequent study of surgery, medicine, pathology and the other clinical disciplines. In recent decades, despite the decrease in the number of hours students spend in an anatomy course, teaching methods in anatomy have improved. The major shift has been towards integration of clinical problems into the anatomy course. Problem based learning (PBL) has proved to be a very successful method for teaching medical students not only in basic sciences but also in developing problem solving skills and interpersonal relationships. The specific objectives listed in the following pages are intended to encourage students to actively take part in deriving the answers from the cases. Each case study is based on the clinical presentations, in which the detail has been re-focused to draw attention to specific anatomical regions. This book, emphasizing the applied aspects can be used as a supplement to existing classes in Gross Anatomy. This suite of programs attempts to bridge the gap between pre-clinical and clinical medicine. This book is not intended to be a replacement for a good textbook. It has been constructed.....not to save the student from taking the trouble to learn clinical anatomy but to encourage the student to take the trouble and save the taking of unnecessary trouble. We hope that this document should serve as the benchmark for anatomical knowledge and Medical students (preclinical and clinical), Allied health science students (physiotherapy students) and those who study this book will find it worthful.